In Sons and Lovers, The Reader's Response was Analyzed in Feminist Perspective - Fouad Abbas (Indonesian Journal of Humanities and Social Sciences, 2023)
This article investigates reader responses to the classic literary work "Sons and Lovers" by D.H. Lawrence using a feminist perspective. Through a literary analysis approach, this research explores how readers respond to feminist aspects in the novel, particularly in the context of resisting patriarchal views. The article provides background information on D.H. Lawrence's life and how his personal experiences are reflected in this work, with an emphasis on feminist elements within the narrative. The research methodology involves in-depth textual analysis and a survey of reader responses to understand how women in the story challenge patriarchal norms and how readers, especially from a feminist perspective, perceive and interpret the involvement of female characters. In the context of feminist theory, this research discusses how "Sons and Lovers" presents a portrayal of power dynamics and gender inequality, as well as how female characters in the novel attempt to resist or adapt to existing social norms. The research findings are expected to provide insights into the impact of feminist theory on readers' understanding and responses to literary works, particularly in the context of "Sons and Lovers. In conclusion, this research delved into the exploration of D.H. Lawrence's "Sons and Lovers" through the lens of reader-response theory, revealing the pivotal role of the reader's experience, knowledge, and cultural background in shaping their perception of the literary work. The initial section provided a contextual backdrop by elucidating Lawrence's personal and societal milieu, emphasizing the autobiographical aspects intertwined with the broader human experience.